If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (q + 1)(2q + -3) = 3 Reorder the terms: (1 + q)(2q + -3) = 3 Reorder the terms: (1 + q)(-3 + 2q) = 3 Multiply (1 + q) * (-3 + 2q) (1(-3 + 2q) + q(-3 + 2q)) = 3 ((-3 * 1 + 2q * 1) + q(-3 + 2q)) = 3 ((-3 + 2q) + q(-3 + 2q)) = 3 (-3 + 2q + (-3 * q + 2q * q)) = 3 (-3 + 2q + (-3q + 2q2)) = 3 Combine like terms: 2q + -3q = -1q (-3 + -1q + 2q2) = 3 Solving -3 + -1q + 2q2 = 3 Solving for variable 'q'. Reorder the terms: -3 + -3 + -1q + 2q2 = 3 + -3 Combine like terms: -3 + -3 = -6 -6 + -1q + 2q2 = 3 + -3 Combine like terms: 3 + -3 = 0 -6 + -1q + 2q2 = 0 Factor a trinomial. (-3 + -2q)(2 + -1q) = 0Subproblem 1
Set the factor '(-3 + -2q)' equal to zero and attempt to solve: Simplifying -3 + -2q = 0 Solving -3 + -2q = 0 Move all terms containing q to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -2q = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -2q = 0 + 3 -2q = 0 + 3 Combine like terms: 0 + 3 = 3 -2q = 3 Divide each side by '-2'. q = -1.5 Simplifying q = -1.5Subproblem 2
Set the factor '(2 + -1q)' equal to zero and attempt to solve: Simplifying 2 + -1q = 0 Solving 2 + -1q = 0 Move all terms containing q to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1q = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1q = 0 + -2 -1q = 0 + -2 Combine like terms: 0 + -2 = -2 -1q = -2 Divide each side by '-1'. q = 2 Simplifying q = 2Solution
q = {-1.5, 2}
| 2x+4=3x-10 | | 9(h-84)-5=77 | | (7y)/(7y+7)+(7y-17)/(6y+6)=(6y+1)/(y+1) | | |36-7|=27 | | o/9+13=-3 | | 0/9+13=-3 | | 2/3v+1/6-7/9-5/6 | | 7y/(7y+7)+(7y-17)/(6y+6)=(6y+1)/(y+1) | | (31/5)y=31 | | 5N(N-1)=N+8 | | 12-9x=17-8x | | 31/5y=31 | | |x-5|+2=9 | | |x-5|-2=9 | | u/2-10=-80 | | 3b^2-b-1=0 | | h/2=-70 | | x+7/x+5 | | 4p^2-4p=0 | | -2.3a+16=-5a-38 | | 10x-27=7x+54 | | (14-y)=12 | | 2x+1=3x-8 | | 8(3x-5)=38 | | 3(6-d)=18 | | 1.2x+3.7=2.2-4.5 | | 6h-7=-73 | | -1r=6 | | x^2y^2=2x | | ln(x)+5=0 | | (5)(-10)= | | x-8y=-11 |